Defense response to caterpillar feeding stress in wild Pinus tabuliformis unveiled by quantitative integrated proteomic and phosphoproteomic analyses - Sun, Tianhua; Zhao, Yanan; Zhou, Guona; Gao, Suhong; Liu, Junxia; Gao, Baojia (Frontiers in Forests and Global Change, 2024)
Pinus is a genus of great economic and ecological importance, and its members are dominant components of forests throughout the world. During the long evolutionary “arms race,” plants have developed complex and diverse systemic defense mechanisms to strategically and intelligently compete with herbivores. To study the alteration pattern and defensive response mechanism triggered by herbivorous feeding stimuli, we firstly built a biological model of the interrelationship between the Chinese pine (Pinus tabuliformis Carr.) and the Chinese pine caterpillar (Dendrolimus tabulaeformis Tsai et Liu). This model integrated proteomic and phosphoproteomic data, which were then normalized and combined with bioinformatics tools to evaluate and analyze changes in the phosphoproteomic profile in response to the caterpillar’s feeding stimulus on pine needles. Systematic identification of differentially significant phosphorylated proteins implicated in the pine’s defense mechanism against caterpillar stress was conducted. Furthermore, we predicted upstream kinases of phosphorylation sites and their activities. Through an analysis of Motif patterns of phosphorylated proteins, Mfuzz clustering of phosphorylation sites, and kinase regulatory networks, we explored the functional modules of phosphorylated protein interaction networks in response to stress within pine. In general, our study emphasized the significant role of kinase METK2, PTI12, PGK, as well as At3g59480 for the first time. The identification of these phosphorylated proteins was additionally confirmed through parallel reaction monitoring technology. Furthermore, genes associated with differentially expressed proteins were validated through real-time quantitative polymerase chain reaction detection. This investigation aids in understanding the mechanisms behind resistance formation and regulation of caterpillar feeding incentives in pine. Breeding more resistant pine varieties may benefit from a fuller understanding of these defense strategies in the future.